TEACHING ENGLISH IDIOMS AND PHRASAL VERBS: PROBLEMS AND SOLUTIONS IN UZBEK CLASSROOMS - Zokirova Marjona Xislatjon qizi (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Annotation: Teaching English idioms and phrasal verbs presents a significant challenge in Uzbek classrooms due to linguistic and cultural differences. This paper examines the most common difficulties faced by both teachers and learners when dealing with idiomatic expressions and multi-word verbs. Based on classroom observations, teacher interviews, and student feedback, the study identifies major problems such as lack of contextual understanding, limited exposure, and ineffective teaching strategies. It also explores practical solutions, including the use of visual aids, storytelling, contextual learning, and digital resources. The findings highlight the importance of culturally aware and communicative approaches in helping Uzbek learners grasp and use idioms and phrasal verbs effectively.